Neutropenic Enterocolitis and Sepsis: Towards the Definition of a Pathologic Profile - Giuseppe Bertozzi; Aniello Maiese; Giovanna Passaro; Alberto Tosoni; Antonio Mirijello; Stefania De Simone; Benedetta Baldari; Luigi Cipolloni; Raffaele La Russa (Medicina, 2021)
Background: Neutropenic enterocolitis (NE), which in the past was also known as typhlitis or ileocecal syndrome for the segment of the gastrointestinal tract most affected, is a nosological entity that is difficult to diagnose and whose pathogenesis is not fully known to date. Initially described in pediatric patients with leukemic diseases, it has been gradually reported in adults with hematological malignancies and non-hematological conditions, such as leukemia, lymphoma, multiple myeloma, aplastic anemia, and also myelodysplastic syndromes, as well as being associated with other immunosuppressive causes such as AIDS treatment, therapy for solid tumors, and organ transplantation. Therefore, it is associated with high mortality due to the rapid evolution in worse clinical pictures: rapid progression to ischemia, necrosis, hemorrhage, perforation, multisystem organ failure, and sepsis. Case report: A case report is included to exemplify the clinical profile of patients with NE who develop sepsis. Literature Review: To identify a specific profile of subjects affected by neutropenic enterocolitis and the entity of the clinical condition most frequently associated with septic evolution, a systematic review of the literature was conducted. The inclusion criteria were as follows: English language, full-text availability, human subjects, and adult subjects. Finally, the papers were selected after the evaluation of the title and abstract to evaluate their congruity with the subject of this manuscript. Following these procedures, 19 eligible empirical studies were included in the present review. Conclusions: Despite the recent interest and the growing number of publications targeting sepsis and intending to identify biomarkers useful for its diagnosis, prognosis, and for the understanding of its pathogenesis, and especially for multi-organ dysfunction, and despite the extensive research period of the literature review, the number of publications on the topic “neutropenic enterocolitis and sepsis” appears to be very small. In any case, the extrapolated data allowed us to conclude that the integration of medical history, clinical and laboratory data, radiological imaging, and macroscopic and histological investigations can allow us to identify a specific pathological profile.